Research Design: Qualitative, Quantitative and Mixed Methods Approaches - Guardiola Corral, Verónica (COMUNICACIÓN. Revista Internacional de Comunicación Audiovisual, Publicidad y Estudios Culturales, 2022)
Research Design: Qualitative, Quantitative and Mixed Methods Approaches. John W. Creswell California, SAGE, 2003, 246 páginas